Expanding Tele-Psychiatry: Virtual Mental Health Support in Underserved Regions - Deepa Mogilivaripalli Kurapathi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Tele-psychiatry is bringing in a shift in mental health care especially in the underserved areas. It also helps bridge gaps such as physical, social, geographic, and financial. They have revealed that Augmented Reality enhances the aspects of accessibility and patients’ experiences significantly. However, there are some issues associated with it such as technology constraints and legal issues. Conventional care can occur virtually to a considerable extent while supplementing it with some face-to-face interactions which may be more effective. It can be thus expanded in the future with AI and further developments in the programs for digital literacy. Expansion of tele-psychiatry in different countries can only be attained through implementation of policies and collaboration with private organizations.
Keywords: Tele-psychiatry; Underserved regions; Virtual mental health; Digital healthcare; Mental health accessibility; Telehealth policy